2013
DOI: 10.7819/rbgn.v15i46.1175
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Scorecard: an empirical study of small and medium size enterprises

Abstract: Balanced Scorecard: an empirical study of small and medium size enterprises Palabras clave: Evaluación desempeño. PYME. Portugal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 82 publications
5
15
1
2
Order By: Relevance
“…Several authors argue that it is not only necessary to study the utilization rate of the management accounting methods, but also their dissemination within the corporate environment (Dearman and Shields, 2001;Machado, 2013;Nassar et al, 2011). Dearman and Shields (2001) concluded, through an experimental study, that even when using methods considered as theoretically inadequate, those in charge can make good management decisions, as long as they know the most appropriate alternative methods.…”
Section: -Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors argue that it is not only necessary to study the utilization rate of the management accounting methods, but also their dissemination within the corporate environment (Dearman and Shields, 2001;Machado, 2013;Nassar et al, 2011). Dearman and Shields (2001) concluded, through an experimental study, that even when using methods considered as theoretically inadequate, those in charge can make good management decisions, as long as they know the most appropriate alternative methods.…”
Section: -Literature Reviewmentioning
confidence: 99%
“…Regarding the second group of variables responsible for disseminating the management accounting methods, several authors (Clarke et al, 1999;Cohen et al, 2005;Machado 2012Machado , 2013 have analyzed some financial officers' characteristics such as the educational background, gender and age. Clarke et al, (1999) concluded that the officers' poor educational background is one of the main inhibitors to change in the methods used by the Irish companies.…”
Section: -Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations